Analyzing Malay Stemmer Performance towards Fuzzy Logic Ranking Function on Malay Text Corpus - Rodzman, SB; Ronie, MFIA; Ismail, NK; Abd Rahman, N; Ahmad, F; Nor, ZM (IEEE, 2024)
Indexed by WOS/SCOPUS